APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES - Rahmawati, Imas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Mathematics is the science of logic about shapes, structures, quantities, and concepts related to one another, divided into three fields, namely algebra, analysis, and geometry. The purpose of this study is to describe the application of the Problem Based Learning (PBL) model that can improve student learning outcomes in the material of flat areas in Class VI SD Negeri 34 Babussalam. The research method used was classroom action research (CAR), which was carried out in two cycles. For data collection, student and teacher activity data were collected by direct observation in the classroom. Student learning outcomes data were collected by giving tests to students. The data collected were analyzed descriptively and quantitatively. Based on the analysis, it was found that the basic average score of students was 60.3. After improvement in the first cycle, the average score increased to 73.4, and in the second cycle increased again to 80.3. Regarding students who achieved completeness, in the initial data, 13 students or 48.2% completed the material, while 14 students or 51.8% did not. In the first cycle, 19 students or 70.3% completed, while 8 students or 29.7% did not. In Cycle II, 22 students or 81.4% completed, while 5 students or 18.6% did not. It can be concluded that the application of the Problem Based Learning (PBL) model can improve student mathematics learning outcomes at SDN 34 Babussalam.